Concomitant carriage of KPC-producing and non-KPC-producing Klebsiella pneumoniae ST512 within a single patient. (9th May 2020) - Jousset, Agnès B; Bonnin, Rémy A; Takissian, Julie; Girlich, Delphine; Mihaila, Liliana; Cabanel, Nicolas; Dortet, Laurent; Glaser, Philippe; Naas, Thierry
Abstract: Background: KPC-producing Klebsiella pneumoniae of clonal group 258 are prominent in healthcare settings in many regions of the world. The bla KPC gene is mostly carried by a multireplicon IncFIIk -IncFI plasmid suspected to be highly compatible and stable in this genetic background. Here, we analysed the genetic diversity of an ST512 K. pneumoniae population in a single patient. Methods: Twelve K. pneumoniae isolates ( n = 5 from urine samples and n = 7 from rectal swabs) were recovered from one patient over a 2 month period. Antimicrobial susceptibility testing, plasmid extraction and WGS were performed on all isolates. The first K. pneumoniae isolate, D1, was used as a reference for phylogenetic analysis. Results: Antimicrobial susceptibility testing, plasmid analysis and WGS revealed concomitant carriage of carbapenem-resistant and carbapenem-susceptible K. pneumoniae isolates of ST512, with the absence of the entire bla KPC -carrying plasmid in the susceptible population. Furthermore, 14 other genetic events occurred within the genome, including 3 chromosomal deletions (of 71 kb, 33 kb and 11 bp), 2 different insertions of IS Kpn26 and 9 SNPs. Interestingly, most of the events occurred in the same chromosomal region that has been deleted independently several times, probably after homologous recombination involving 259 bp repeated sequences. Conclusions: Our study revealed (to the best of our knowledge) the first case of in vivo bla KPC -carrying plasmid curing and a wide within-patient genetic diversity of a single K. pneumoniae ST512 clone over a short period of carriage. This within-patient diversity must be taken into account when characterizing transmission chains using WGS during nosocomial outbreaks.